Comparative study of anion removal using adsorbents prepared from a homoionic clay - Adauto A. (2021)
The adsorption capacity of adsorbent materials (organophilic clays) prepared from a homoionic clay was compared for the removal of nitrates and nitrites present in aqueous solution in batch systems at room temperature.The organophilic clays were obtained by replacing the exchange cations present in the precursor clays with quaternary ammonium cations. For this purpose, two precursor clays were used, a natural clay (FS) and the same clay exchanged with sodium (CP) and two ammonium cations with different structure: hexadecyltrimethylammonium (HDTMA) and benzyltriethylammonium (BTEA) with amounts equivalent to 1.5, 2.5 and 4.0 cation exchange capacity (C.E.C.). Ion exchange is important to obtain a good affinity between organoclay and anionic contaminants. The clays were characterized by XRD, FTIR and SEM-EDX. The maximum adsorption capacities of the CP-HDTMA-4.0 clay for nitrate and nitrite ion were 7.23 and 0.65 mg g−1, respectively, indicating that the organophilic clay obtained from the homoionic clay with 4 C.E.C. ion exchange and the surfactant HDTMA had significant effects on the adsorption of nitrate and nitrite ions. Finally, the possible mechanisms and implications of the results for the use of these organophilic clays as adsorbent materials for the removal of the ions under study are discussed.